Molecular taxonolny of Hypsibarbus spp. in penisular Malaysia: A preliminary study. - Md. Naim, Darlina

(untitled)
The tropical Asian cyprinid, genus Hypsibarbus is widely distributed in the freshwater habitats throughout Southeast Asia. Record on systematic status of the endangered genus Hypsibarbus in Malaysia has not been well documented.